School attendance and child labor: A model of collective behavior - Holger Strulik (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2010)
This paper theoretically investigates how community approval or disapproval affects school attendance and child labor and how aggregate behavior of the community feeds back towards the formation and persistence of an anti- (or pro-) schooling norm. The proposed community-model continues to take aggregate and idiosyncratic poverty into account as an important driver of low school attendance and child labor. But it provides also an explanation for why equally poor villages or regions can display different attitudes towards schooling. Distinguishing between three different modes of child time allocation, school attendance, work, and leisure, the paper shows how the time costs of schooling and child labor productivity contribute to the existence of a locally stable anti-schooling norm. It proposes policies that effectively exploit the social dynamics and initiate a permanent escape from the anti-schooling equilibrium. An extension of the model explores how an education contingent subsidy paid to the poorest families of a community manages to initiate a bandwagon effect towards 'education for all'. The optimal mechanism design of such a targeted transfer program is investigated.
Keywords: I20; I29; J13; O12; 330; School Attendance; Child Labor; Social Norms; Targeted Transfers; Bildungsverhalten; Kinder; Kinderarbeit; Haushaltsökonomik; Zeitallokation; Gemeinschaft; Soziale Werte; Public Choice; Armutspolitik; Bildungspolitik; Konsuminterdependenz; Theorie